Synthesis of (S)-FTY720 vinylphosphonate analogues and evaluation of their potential as sphingosine kinase 1 inhibitors and activators - Liu, Zheng (2013)
Sphingosine kinase 1 (SK1) is over-expressed in many cancers where it provides a selective growth and survival advantage to these cells. SK1 is thus a target for anti-cancer agents that can promote apoptosis of cancer cells. In previous work, we synthesized a novel allosteric SK1 inhibitor, (S)-FTY720 vinylphosphonate. We now report a more expeditious route to this inhibitor which features B-alkyl Suzuki coupling as a key step and show that replacement of the amino group in (S)-FTY720 vinylphosphonate with an azido group converts the vinylphosphonate from an allosteric inhibitor to an activator of SK1 at low micromolar concentrations. Our results demonstrate the feasibility of using the (S)-FTY720 vinylphosphonate scaffold to define structure-activity relationships in the allosteric site of SK1.